Ceci n’est pas une pipe. The architectural drawing between representation and function - Pedersen, Claus Peder; Oxvig, Henrik (Enquiry The ARCC Journal for Architectural Research, 2007)
In The Sciences of the Artificial Herbert A. Simon reflects that "Engineering, medicine, business, architecture, and painting are concerned not with the necessary but with the contingent – not with how things are but with how they might be – in short, with design.” The reflection serves as an introduction to Simon’s attempt at developing a design theory: A theory about the conception of that which differs from what we already know. A theory in a challenged dialog with the contingent. Simon is aware that traditionally, design theory has been orientated towards the establishment of an understanding of the canonized and typical, and that the theory as such should serve as a guideline for what was to be created. Traditionally, the theory has been a reflected list of answers. By way of example, consider how the Neo-Platonic architecture treaties of the Renaissance sought to establish abstract and ideal rules and frameworks to secure any future works. Through repetition of the regular, the work becomes an example of a presumed eternal and essentially true idea. Or consider the ambitions of the modernist town planning, as they were expressed in the resolutions of CIAM as well as in concrete town planning proposals, in which the specific purpose was to transform the town’s quantitative environment into qualitative by means of ‘abstraction and repetition’. The architects of modernism and the Renaissance shared a confidence in the possibilities of the abstraction to establish a template for the individual example. Consequently, both lines of thinking demonstrate confidence that by means of mathematics and the Euclidian geometry, an essential world structure is found which may justify the qualitative validity of abstract rules. And that is precisely why the repetition of the structures and types of the abstraction becomes a design-theoretical imperative. Whilst the Renaissance treaties gave the impression of being carried by an insight into the world’s eternal – divine – structure, the modernists were orientated towards the technological or the natural. However, to some extent the rules were the same, as Colin Rowe pointed out in his famous article, ‘The Mathematics of the Ideal Villa’. Rowe compares– in continuation of Rudolf Wittkower’s Renaissance studies – Palladio’s and Le Corbusier’s basic plans for villas and demonstrates remarkable similarities between the syntactic geometric organizational principles of the plans. To a certain degree, modernism naturalizes the divinely founded rules of the Renaissance. And because of this, it gives rise to expectations that, as is the case with the Renaissance treatises, architectural theory should develop ideas and rules that are valid for the concrete assignment, notwithstanding that they – the rules – are developed in abstract independence of any contingent situation.Those are the types of expectations to the theory that Simon argues against when insisting that the work is contingent. He claims that the individual work differs unpredictably from the rules and typologies that existed prior to the work. However, Simon’s skepticism towards normative design theories does not imply that he finds theoretical work irrelevant for the creation of the contingent. On the contrary, Simon’s ambition is to establish a mutual experimental relation between theory and practice.